Determinants of the Use of Cashless Transactions in Culinary MSME Consumers in Tebing Tinggi City - Putri Safa Aulia Lubis; Atika Atikah; Nurul Inayah (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
Multiple linear regression analysis is one of the quantitative techniques used in this study. The data was processed using SPSS version 22. The population of this study is the people of Tebing Tinggi who use cashless transactions as a payment method for culinary MSMEs. The sample in this study amounted to 96 people. This study aims to find out the convenience, benefits, and digital literacy that affect individually and simultaneously the use of cashless transactions in culinary MSME consumers in the city of Tebing Tinggi. The analysis of the study shows that convenience has a positive and significant influence on the use of cashless transactions. Usefulness also has a positive and significant influence on the use of cashless transactions, while digital literacy has no influence on the use of cashless transactions. Convenience, Usefulness, and Digital Literacy simultaneously affect the use of cashless transactions.